Writing useful, accessible, and legally defensible psychoeducational reports - Hass, Michael R.; Carriere, Jeanne Anne M. (Hoboken, New Jersey : Wiley, 2014)
'This important new resource offers practical guidance on writing psychoeducational reports that directly respond to referral concerns. The authors provide recommendations and assessment information in a format easily understood by parents, teachers, and other educational and mental health professionals. Filled with numerous practice exercises, sample reports, helpful checklists, and end of chapter questions, this invaluable guide provides an approach to writing reports that will help school psychologists better meet the needs of the individualized education program (IEP) team, teachers, parents, and others working with the child'--
Machine generated contents note: Acknowledgements Chapter 1 Why Is Another Book on Report Writing Needed? Chapter 2 What Makes a Report Legally Defensible? Chapter 3 How Do I Make a Report More Useful to Consumers? Chapter 4 Step by Step, How Do I Write Useful and Legally Defensible Reports? Chapter 5 How do I solve practical problems along the way to question-driven report writing? Appendix I -- A Checklist to tell if My Report is Useful and Legally Defensible Appendix II -- What Do These Reports Look Like? Appendix III -- Interview protocol References .
Includes bibliographical references (pages 173-180) and indexes.
Keywords: Individualized education programs; Report writing; Children with disabilities -- Education -- Evaluation